2008
DOI: 10.5902/19805098456
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de hipoclorito de sódio na esterilização de meio de cultura para multiplicação in vitro de <i>Eucalyptus pellita </i>L.

Abstract: Ultimamente, vem-se observando grande interesse na área de pesquisa em cultura de tecidos vegetais, em se descobrir novas opções que resultem na redução dos custos da micropropagação das plantas em laboratórios comerciais, de modo a torná-la mais viável economicamente. Uma opção potencialmente promissora para a redução de custos, mas que não tem recebido a devida atenção, é a perspectiva de se substituir a técnica de autoclavagem por outra mais econômica. Com esse objetivo, foram realizados dois testes utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 1 publication
0
14
1
9
Order By: Relevance
“…Studies on NaClO have shown that the application of diluted solution often promotes superior growth of in vitro tissues of different plant species (Chun et al, 1997;Ervin & Wetzel, 2002;Teixeira et al, 2008). However, in our study, increased doses of NaClO had a harmful effect, most likely due to the decontaminant toxicity as the concentration increased.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Studies on NaClO have shown that the application of diluted solution often promotes superior growth of in vitro tissues of different plant species (Chun et al, 1997;Ervin & Wetzel, 2002;Teixeira et al, 2008). However, in our study, increased doses of NaClO had a harmful effect, most likely due to the decontaminant toxicity as the concentration increased.…”
Section: Resultscontrasting
confidence: 56%
“…Studies involving the use of sodium hypochlorite (NaClO) have clearly shown how it can be used as diluted solution, often promoting better growth of in vitro tissues, as verified in the germination of rice (Chun et al, 1997), orchid seeds (Alvarez-Pardo et al, 2006;Rodrigues et al, 2011), and the cloning of Eucalyptus (Teixeira et al, 2008). Teixeira et al (2006) used weak solutions of NaClO (1, 3, 5, 7 and 9 mg L -1 ) added to culture media to control contamination in banana.…”
Section: Introductionmentioning
confidence: 99%
“…Media that use MS salts are usually supplemented with organic additives, including some that are constituents of MS medium (e.g., 500-555 µM myo-inositol, 1-6.25 µM thiamine-HCl, 4.06 µM nicotinic acid, 2.43 µM pyridoxine-HCl, and/or 26.64 µM glycine) and some that are not (e.g., 0.4 µM biotin and/or 0.2 µM calcium pantothenate). Other proliferation media for eucalypts have included woody plant medium (WPM) [94,97], JADS media [98][99][100], DKW medium [101], mixtures of MS and de Fossard nutrients [102], and MS basal salts with either White vitamins or B5 vitamins [85,87,90,103]. Shoot proliferation is performed in the light, usually on semi-solid medium containing 58.4 mM or 87.6 mM sucrose (Table A1).…”
Section: Shoot Culturementioning
confidence: 99%
“…O hipoclorito de sódio (NaClO) é um produto com atividade biocida, de baixo custo e que se apresenta como alternativa à autoclavagem, que é uma operação dispendiosa e com elevado consumo de energia elétrica (EMMANUEL et al, 2004). Além disso, diversos trabalhos têm apresentado bons resultados com a utilização do NaClO como agente químico esterilizante no cultivo in vitro de diversas espécies (TEIXEIRA et al, 2006;TEIXEIRA, 2007;TEIXEIRA et al, 2008).…”
Section: Starch and Sodium Hipochlorite On In Vitro Rooting Of Pineapunclassified